The Image of Recipient of Journalistic Text Within Newspaper Headlines - Baklanova, Irina (Przegląd Wschodnioeuropejski, 2019)
The article is focused on the revealing of the intended recipient image which is reflected implicitly in a journalistic text. The aim of the article is to identify the sources of information about the intended recipient image of newspaper headlines basing on Grice’s verbal communication maxims. The study continues similar work carried out on the material of the other types of non-fiction text: memoirs, scientific and advertising. The research results seem significant in determining the circle of potential recipients of various newspaper and magazine publications and editing the publications taking into account the anticipated readers.